2018
DOI: 10.1097/scs.0000000000004521
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of an Uncommon High-Pressure Orbital Injection Injury

Abstract: Injection injuries occur most commonly in the hand and digits; however, there are a limited number of reports in the literature describing injection injuries involving the orbit. High-pressure orbital injection injuries pose a number of unique challenges to the treating physician, and the approach to treating these injuries remains controversial. Often times, the extent of tissue damage is not fully appreciated at presentation, which may lead to missed diagnoses or inadequate initial treatment. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Clinical manifestations of orbital infection usually involve periorbital edema, crepitus, ophthalmoplegia, exophthalmos, chemosis, and visual loss [2, 7]. The case we have reported here had no other specific features, and the symptoms mentioned above are similar to those for subacute local infection.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Clinical manifestations of orbital infection usually involve periorbital edema, crepitus, ophthalmoplegia, exophthalmos, chemosis, and visual loss [2, 7]. The case we have reported here had no other specific features, and the symptoms mentioned above are similar to those for subacute local infection.…”
Section: Discussionsupporting
confidence: 59%
“…The patient in this case had no obvious immunodeficiency and was infected due to traumatic orbital injury. Infection by direct orbital injury is rare, as most injury-mediated infections occur in the limbs and skin [2]. According to Torres et al, a literature review of nocardiosis showed that traumatic injuries accounted for only 10% of infections [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 11 , 12 ] Once the infection occurs, the onset of disease is acute, but the development is rapid with strong invasiveness, severe tissue destruction and long course of treatment. [ 13 ] The patient in this study is a decoration worker. Because foreign bodies (e.g., soil) often collapsed into the eye, and the left cornea had punctate foreign body residues, it is suspected that the patient had infectious scleritis involving the corneal limbus caused by N. farcinica from the trauma wound.…”
Section: Discussionmentioning
confidence: 99%